Edukasi dan Skrining Hemoglobin sebagai Upaya Pencegahan Anemia pada Remaja: Education and Hemoglobin Screening as an Effort to Prevent Anemia In Adolescents - Aida Kusnaningsih; Reny Sulistyowati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Anemia is a health condition that can affect adolescents. Anemia is a condition in which the number of red blood cells and hemoglobin levels is lower than normal. Efforts to prevent anemia can be made by increasing knowledge about anemia and conducting early detection of anemia. The community service activities included health education on anemia and on detecting it through hemoglobin (Hb) level testing. The activities aimed to improve the health of adolescent girls through early detection of anemia, anemia education, and brain health. Thirty female students participated in the activities. The health education was conducted through a lecture and question-and-answer method, with an LCD projector, slides, and booklets. Early detection of anemia involved hemoglobin testing using an Hb meter and peripheral blood samples. The activities ran smoothly, with all participants enthusiastically participating from beginning to end. Evaluation results showed that 30 (100%) participants did not experience anemia. The level of knowledge about anemia before the anemia education was mostly at a sufficient level (17 students (56.7%), and after the education, all 30 (100%) participants had a good level of knowledge. The activity provided benefits, increasing knowledge from fair to good, and providing baseline data on the incidence of anemia in adolescent girls.